Management of third apical fracture in anterior teeth with apical resection - Yuliana Sari; Tunjung Nugraheni; Wignyo Hadriyanto; Dessy Natalia (Journal of Dentomaxillofacial Science, 2021)
Objective: Tooth fractures are mostly caused by traumatic injuries that can involve the pulp and surrounding periodontal tissue. Root fracture is an unusual injury (0,5-7%) but requires a complex healing pattern, so the treatment can require many specialists. Fractures at the third level have a good result if the proper diagnosis and there is no mobility and the teeth are asymptomatic. Case Report: Treatment of this third-apical fractures is endodontics treatment in the coronal and apical resection of the apical fragmen with MTA placement to get an apical plug. The treatment is continued by prosthodontic to obtain the aesthetic result. Results: Endodontic treatment and apical resection presented good results with no symptoms of clinical pathology for about 3 months followed up. Conclusion: Fractures at the third level have a good result if the proper diagnosis, the rightÂ treatment planning and procedures are performed.